Renal parenchymal volume analysis: Clinical and research applications - Carlos Munoz‐Lopez; Kieran Lewis; Nityam Rathi; Eran Maina; Akira Kazama; Anne Wong; Angelica Bartholomew; Worapat Attawettayanon; Yunlin Ye; Zhiling Zhang; Wen Dong; Rebecca A. Campbell; et al. (BJUI Compass)
Abstract Background and Objectives In most patients, the renal parenchymal volumes in each kidney directly correlate with function and can be used as a proxy to determine split renal function (SRF). This simple principle forms the basis for parenchymal volume analysis (PVA) with semiautomated software, which can be leveraged to predict SRF and new‐baseline glomerular filtration rate (NBGFR) following nephrectomy. PVA was originally used to evaluate renal transplantation donors and has replaced nuclear renal scans (NRS) in this domain. PVA has subsequently been explored for the management of patients with kidney cancer for whom difficult decisions about radical versus partial nephrectomy can be influenced by accurate prediction of NBGFR. Our objective is to present a comprehensive review of the applications of PVA in urology including their clinical and research implications. Methods Key articles utilizing renal PVA to improve clinical care and facilitate urologic research were reviewed with special emphasis on take‐home points of clinical relevance and their contributions to progress in the field. Results There have been considerable advances in renal PVA over the past 15 years, which is now established as a reference standard for the prediction of functional outcomes after renal surgery. PVA provides improved accuracy when compared to NRS‐based estimates or non‐SRF‐based algorithms. PVA can be performed in minutes using routine preoperative cross‐sectional imaging and can be readily applied at the point of care. Additionally, PVA has important research applications, enabling the precise study of the determinants of functional recovery after partial nephrectomy, which can affect surgical approaches to this procedure. Conclusions Despite the wide availability of PVA, primarily for use in renal transplantation, it has not been widely implemented for other urologic purposes at most centres. Our hope is that this narrative review will increase PVA utilization in urology and facilitate further progress in the field.